2010
DOI: 10.1093/abbs/gmp117
|View full text |Cite
|
Sign up to set email alerts
|

Production of an anti-idiotypic antibody single chain variable fragment vaccine against <italic>Edwardsiella tarda</italic>

Abstract: Edwardsiella tarda is the pathogen responsible for edwardsiellosis, a serious infectious disease of freshwater and marine fish species, and currently recognized to be the species pathogenic for human. An anti-idiotypic monoclonal antibody (mAb), 1E11, has been developed. It mimics the protective epitope of E. tarda and can prevent fish from infection of E. tarda. In this study, the correct variable heavy (V H ) and variable light (V L ) genes were obtained from 1E11 by using bioinformatics methods, and a 15 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The use of anti-idiotype antibody in the control of K88 Eschershia coli (Jaradat et al, 2010), Edwardsiella tarda (Qin et al, 2010), hepatitis B (Yildrim et al, 2004, HIV-1 (Mader and Kunert, 2012), prion diseases (Venturini et al, 2009), cancer (Cerio et al, 2007) and atherosclerosis (Brito et al, 2012) were reported before.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of anti-idiotype antibody in the control of K88 Eschershia coli (Jaradat et al, 2010), Edwardsiella tarda (Qin et al, 2010), hepatitis B (Yildrim et al, 2004, HIV-1 (Mader and Kunert, 2012), prion diseases (Venturini et al, 2009), cancer (Cerio et al, 2007) and atherosclerosis (Brito et al, 2012) were reported before.…”
Section: Discussionmentioning
confidence: 98%
“…Anti-idiotype injection can be an alternative for hyperimmunization with original antigens. Using this method, researchers have been able to produce anti-idiotype antibodies against many toxins, cancers and infectious diseases that can mimic the original antigen specificity (Boutin et al, 1994;Liu et al, 1996;Yildrim et al, 2004;Jaradet et al, 2010;Qin et al, 2010). Idiotype hypotheses and anti-idiotype performance are for cellular and humoral defense (Girdhari et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Peptide linkers that join V H and V L chains together usually vary from 10-30 amino acids in length, and the most common linker is the (Gly 4 Ser) 3 [27]. Some studies have reported that variable regions could be linked in the V L -linker-V H orientation or V H -linker-V L orientation[28], and the latter is more commonly seen. The orientations can affect expression efficiency[29], stability, and antigen binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used restriction enzymes, such as HindIII [16] and XhoI [17], form palindromes after digestion, allowing self-ligation to occur and reducing the ligation efficiency. Two different approaches were commonly used to prevent self-ligation.…”
Section: Discussionmentioning
confidence: 99%